Evaluation of Factors Influencing Fluoride Release from Dental Nanocomposite Materials: A Systematic Review - Alicja Morawska-Wilk; Julia Kensy; Sylwia Kiryk; Agnieszka Kotela; Jan Kiryk; Mateusz Michalak; Natalia Grychowska; Magdalena Fast; Jacek Matys; Maciej Dobrzyński (Nanomaterials)
This systematic review aims to evaluate factors influencing fluoride release from dental nanocomposite materials. A comprehensive database search was conducted in February 2025 using PubMed, Web of Science, and Scopus. The search terms “fluoride release AND nanocomposites” were applied following PRISMA guidelines. Out of 336 initially identified articles, 17 studies met the inclusion criteria and were selected for analysis. Seventeen studies confirmed that fluoride-releasing nanocomposites are effective, with fluoride ion release influenced by material composition, nanofiller type, and storage conditions. Studies showed that acidic environments (pH 4–5.5) significantly enhanced fluoride release, particularly in materials containing nano-CaF2 or fluoridated hydroxyapatite, which responded to pH changes. Quantitative comparisons revealed that daily fluoride release values ranged from <0.1 μg/cm2/day in commercial composites to greater than 6500 μg/cm2/day in BT-based nanocomposites and up to 416,667 μg/cm2/day in modified GICs. Additionally, some composites exhibited fluoride recharging capabilities, with materials incorporating pyromellitic glycerol dimethacrylate (PMGDM) and ethoxylated bisphenol A dimethacrylate (EBPADMA) demonstrating prolonged fluoride and calcium ion release after recharge exposure, rather than the highest initial values. Despite releasing lower fluoride levels than conventional GIC and RMGI materials, fluoride-releasing nanocomposites demonstrate significant anti-caries potential and clinical applicability, with some formulations supporting periodontal regeneration and caries prevention around orthodontic brackets. However, the lack of consistency in study protocols—including differences in storage media, sample geometry, and measurement methods—limits direct comparison of outcomes. Therefore, the most critical direction for future research is the development of standardized testing protocols to ensure reliable, comparable results across material groups.